Conducting Polymer Nanocomposite for Energy Storage and Energy Harvesting Systems - null Sonika; Sushil Kumar Verma; Siddhartha Samanta; Ankit Kumar Srivastava; Sonali Biswas; Rim M. Alsharabi; Shailendra Rajput (Advances in Materials Science and Engineering)
Conducting polymers (CPs) have received a lot of attention because of their unique advantages over popular materials, such as universal and tunable electrical conductivity, simple invention approach, high mechanical strength, low weight, low price, and ease of processing. Polymer nanocomposites have been enthusiastically explored as superlative energy generators for low-power-consuming electronic strategies and confirmed progressive surface area, electronic conductivity, and amazing electrochemical behaviour through expanding the opportunity of utilization. The hybridization of conducting polymer with inorganic hybrid and organic nanomaterials also resulted in multifunctional hybrid nanocomposites with better capabilities in a variety of devices, including sensors, energy storage, energy harvesting, and defensive devices. The capability and assistance of modern advancements for the development of multifunctional nanomaterials/nanocomposites have been presented, as well as the approaches for producing nanostructured CPs. The mechanisms underlying their electrical conductivity, and ways for modifying their properties, are investigated. The ongoing research towards generating superior CP-based nanomaterials is also discussed. This assessment focuses on the important schemes involved in the scientific and industrial use of polymeric materials and nanocomposites intended for the scheme and manufacture of energy strategies such as solar cells, rechargeable batteries, supercapacitors, and energy cells, as well as the waiting problems and their prospects.